2009
DOI: 10.1038/ni.1834
|View full text |Cite
|
Sign up to set email alerts
|

The activating receptor NKp46 is essential for the development of type 1 diabetes

Abstract: The mechanism of action of natural killer (NK) cells in type 1 diabetes is still unknown. Here we show that the activating receptor NKp46 recognizes mouse and human ligands on pancreatic beta cells. NK cells appeared in the pancreas when insulitis progressed to type 1 diabetes, and NKp46 engagement by beta cells led to degranulation of NK cells. NKp46-deficient mice had less development of type 1 diabetes induced by injection of a low dose of streptozotocin. Injection of soluble NKp46 proteins into nonobese di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
219
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(227 citation statements)
references
References 36 publications
6
219
1
1
Order By: Relevance
“…Infected islets were dominated by NK cell infiltration but beta cell function appeared to be preserved. A recent study by Gur and colleagues identified beta cell ligands for the activating NK cell receptor Nkp46 in human and murine pancreas that were shown to be responsible for diabetes development in the NOD mouse [37]. More functional studies of NK cells in early-onset type 1 diabetes are required to determine the effects of the genetic associations described here.…”
Section: Discussionmentioning
confidence: 99%
“…Infected islets were dominated by NK cell infiltration but beta cell function appeared to be preserved. A recent study by Gur and colleagues identified beta cell ligands for the activating NK cell receptor Nkp46 in human and murine pancreas that were shown to be responsible for diabetes development in the NOD mouse [37]. More functional studies of NK cells in early-onset type 1 diabetes are required to determine the effects of the genetic associations described here.…”
Section: Discussionmentioning
confidence: 99%
“…Among the NK cell killer receptors, the NCRs NKp30, NKp44, and NKp46/NCR1, which were discovered more than a decade ago (4), were shown to be paramount to many immunological processes. Specifically, NKp46/NCR1 was implicated in influenza (7,8), tumorigenesis (13), and diabetes (27,28). However, remarkably, other than the influenza virus HA (7) and the pox virus HA (29), no ligands for this important receptor were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the ligand on MCA-transformed cells undergoes immune editing by NKp46/NCR1 pressure (14), whereas the ligand on D122 cells described in this study apparently does not. Finally, we have recently shown that a ligand for NKp46/NCR1 is expressed by human and mouse b cells (27,28), and it was also demonstrated that upon human CMV infection of dendritic cells, an unknown ligand of NKp46/NCR1 is downregulated to prevent NK cell-mediated lysis of the infected dendritic cells (30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…The emerging role of NKp46 is highlighted in studies on mice deficient for Ncr1. These knock-out mice are unable to fight influenza infection, unable to control a specific experimental lymphoma model, and are more protected from development of type 1 diabetes (7)(8)(9).…”
mentioning
confidence: 99%